Goddess beyond boundaries: worshipping the Eternal Mother at a North American Hindu temple - Pintchman, Tracy (Oxford University Press, 2024)
"This book explores the religious life of an American Hindu goddess temple, the Parashakthi Temple, in Pontiac, Michigan. The goddess honored here, Karumariamman, originates from village goddess traditions in South India but comes to assume the status of Great Goddess in her Michigan abode. She is a tantric deity and wonder worker who communicates directly with devotees through dreams, visions, and miracles. The religiosity promoted by the Parashakthi Temple, while clearly Hindu and Indian in both form and substance, is nevertheless grounded in a vision of the Goddess as a breaker of all kinds of boundaries, including those of race, ethnicity, religion, geography, history, and nationality. Temple discourse is deeply innovative both ritually and theologically, reimagining and emplacing the Goddess in the American religious, cultural, and natural landscape and recreating Hindu traditions and the Hindu Great Goddess in dynamic conversation with the new context. Here the Goddess herself embodies the qualities of a new immigrant; she embraces the opportunities her new home affords her and refashions herself, but she does not forget her roots, keeping one foot planted in her Indian homeland and another planted firmly in her new land, the United States"--